If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -21 = -1x * 2 Reorder the terms: -21 + x = -1x * 2 Reorder the terms for easier multiplication: -21 + x = -1 * 2x Multiply -1 * 2 -21 + x = -2x Solving -21 + x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -21 + x + 2x = -2x + 2x Combine like terms: x + 2x = 3x -21 + 3x = -2x + 2x Combine like terms: -2x + 2x = 0 -21 + 3x = 0 Add '21' to each side of the equation. -21 + 21 + 3x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 3x = 0 + 21 3x = 0 + 21 Combine like terms: 0 + 21 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 |